2011
DOI: 10.3813/aaa.918466
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Sound Transmission Loss of Honeycomb Panels using the Wave Propagation Approach

Abstract: The sound transmission properties of sandwich panels can be predicted with sufficient degree of accuracy by calculating the wave propagation properties of the structure. This method works well for sandwich panels with isotropic cores but applications to panels with anisotropic cores are hard to find. Honeycomb is an example of anisotropic material which when used as a core, results in a sandwich panel with anisotropic properties. In this paper, honeycomb panels are treated as being orthotropic and the wavenum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…[37] Fig. 7 Comparison of STL between the present model and results by Kumar et al [24] In addition, since the honeycomb sandwich panel with perforated face plate can be degraded to non-perforated classic honeycomb sandwich panel when the perforation ratio and perforated pore diameter are negligibly small, the present theory is therefore verified by Kumar et al's [24] model for classical honeycomb sandwich panels as shown in Fig. 7.…”
Section: Figsupporting
confidence: 76%
See 1 more Smart Citation
“…[37] Fig. 7 Comparison of STL between the present model and results by Kumar et al [24] In addition, since the honeycomb sandwich panel with perforated face plate can be degraded to non-perforated classic honeycomb sandwich panel when the perforation ratio and perforated pore diameter are negligibly small, the present theory is therefore verified by Kumar et al's [24] model for classical honeycomb sandwich panels as shown in Fig. 7.…”
Section: Figsupporting
confidence: 76%
“…In addition to characterizing their structural behavior, many studies have also been carried out to characterize their vibroacoustic behavior. For typical instance, Kumar et al [24], Jung et al [25], Huang and Ng [26], and Ng and Hui [27] presented theoretical models to predict the STL of honeycomb sandwiches, while Griese et al [28] and Feng and Kumar [29] employed numerical and experimental methods to investigate their STL.…”
Section: Introductionmentioning
confidence: 99%
“…For honeycomb sandwich plates, it is necessary to compare the sound insulation prediction results of finite and infinite sizes. 15 Qian et al predicted the STL of finite sandwich plates with honeycomb cores based on a test procedure on beam elements, and found that the forecast results of the finite large models showed many fluctuations at low frequencies compared with the infinite large models. 16 For the accurate prediction of the STL of honeycomb sandwich plates, the damping caused by acoustic radiation is very important.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, composite structures are a class of interesting products allowing one to combine the properties of various individual materials to obtain a new material with enhanced characteristics. The construction of aerospace structures has historically been one of the driving forces behind the development of advanced composite materials, making large use of foam and honeycomb aluminum panels because of aluminum's high strength-to-weight ratio, energy absorption, heat transfer and electromagnetic shielding properties, combined with good machinability at a relatively low cost [1]; all qualities that spread the diffusion of such structures to the transportation sector, including rail [2] and shipbuilding [3] industries where the characteristics have to satisfy lightweight and structural demands. The characterization of aluminum honeycomb structures has been the subject of many scientific works, especially from the mechanical viewpoint [4,5] and, in recent years, for innovative types of core [6,7] for which experimental results must validate virtual models.…”
Section: Introductionmentioning
confidence: 99%